FAKTOR-FAKTOR YANG MEMPENGARUHI CASH HOLDING DENGAN GCG SEBAGAI VARIABEL MODERASI - Morgan, Christopher Elihu Billy; Viriany, Viriany (Jurnal Paradigma Akuntansi, 2025)
This study aims to analyze the effect of growth opportunity, cash flow, and capital expenditure on cash holding with good corporate governance (GCG) as a moderating variable in plastic and packaging sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) with an observation period of 2019-2021. The sample technique used is purposive sampling where the total sample is 11 companies with a total of 33 data. The analysis technique used in this study is moderating regression analysis using Eviews 12 for students to process data and Microsoft Excel 2010 to collect data. The results shown in this study indicate that growth opportunity and cash flow have a positive and significant effect on cash holdings, while capital expenditure has a negative and insignificant effect on cash holdings. GCG moderates the effect of growth opportunity on cash holding, while GCG does not moderate the effect of cash flow and capital expenditure on cash holding. The implication of this research is the need for increased board of commissioners meetings to increase growth opportunities which will increase cash holdings for better financial management by companies.